Estimasi Produksi Usahatani Kentang (Estimation Of Potato Farm Production) - Ri Esso, Andi Sawe (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2018)
This study aims to determine the analysis of factors that affect the production of farming. This study uses primary data obtained through direct interviews, analyzed by multiple regression model using SPSS Statistic 21 program. Variables that have an influence on the production of potato farming in this study is Seed Volume has a negative and significant effect on potato production, land area has a positive and significant impact on potato production, and dummy areas have a negative and significant effect on potato production.